PERILAKU SHARING KONTEN ONLINE: FAKTOR MOTIVASI INDIVIDUAL DAN PENGARUH MODERASI FAKTOR SITUASIONAL - Yessy Artanti; Sri Hartini (Jurnal Manajemen dan Pemasaran Jasa, 2019)
Online information sharing behavior is an activity of exchanging or sharing information quickly and widely, as well as viruses on a computer, using interactive internet networks. To comprehensively comprehend the process of social transmission and the factors that influence it, it is necessary to know the variables that affect social relations. Previous studies have still little to discuss the role of social processes that encourage individuals to decide on the affinity of online content sharing. In addition, there are still not many studies that emphasize what kind of online content causes content to be more viral than other types of content supported by individual motivational factors and some variables that can strengthen or even weaken that influence. This research uses 208 student respondents through the Moderated Regression Analysis tool to examine situational factors as moderator variables on the relationship between individual motivational factors and online content sharing behavior. The results of the analysis found that there were significant effects of individual motivational factors on online content sharing behavior but this effect became not significant in the presence of situational factors as moderator variables. This research contributes significantly to marketing strategies in a company by utilizing the type of content and individual motivational factors that cause viral content or news to be faster.